Penerapan Algoritma K-Means Untuk Clustering Bakery Dan Cake Yang Laris - Ahmad Fachriansyah; Efori Bu'ulolo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Bakery and Cake is a business engaged in the production of cakes, pastries and bread. Syahfira Bakery and Cake shop is a cake, sponge and bread shop which so far has not utilized data to determine store business strategy. The development of a business is based on good product sales marketing, this is inseparable from service between sellers and buyers as well as good relations between company owners and employees, this is the main key in a company. On this occasion the author will conduct research using the k-means algorithm for clustering bakeries and cakes which are in demand at CV. Syahfira Bakery and Cake by utilizing existing data that has been processed into excel data and cashier sales books. Based on the data previously obtained, there are six products that will be clustered on iteration or grouping calculations. With these data, the two best-selling products were obtained after calculating the application of the k-means algorithm, namely Cheese Wrap Bread and Chocolate Cheese Wrap Bread because they got a position in cluster 1